Potamalpheops tyrymembe sp. n.: the first southwestern Atlantic species of the shrimp genus Potamalpheops Powell, 1979 (Caridea: Alpheidae) - Soledade, Guidomar O.; Santos, Patricia S.; Almeida, Alexandre O. (Zootaxa, 2014)
A new species of the alpheid shrimp genus Potamalpheops Powell, 1979, P. tyrymembe sp. n., is described based on several specimens collected from burrows of the ucidid crab Ucides cordatus (Linnaeus, 1763) and other, unknown burrowing decapods, on a mangrove flat between the Baiano and Serra rivers, Povoado de Tremembé, Maraú, state of Bahia, Brazil (14º08’51.9”S, 39º05’04.4”W). The new species belongs to the P. monodi (Sollaud, 1932) species group, based on the presence of two pairs of spiniform setae on the distal margin of the telson and non-enlarged male chelipeds. It is characterized by a short rostrum and absence of setae on the pterygostomial angle of the carapace.